2016
DOI: 10.1186/s12885-016-2055-1
|View full text |Cite
|
Sign up to set email alerts
|

A potent betulinic acid analogue ascertains an antagonistic mechanism between autophagy and proteasomal degradation pathway in HT-29 cells

Abstract: BackgroundBetulinic acid (BA), a member of pentacyclic triterpenes has shown important biological activities like anti-bacterial, anti-malarial, anti-inflammatory and most interestingly anticancer property. To overcome its poor aqueous solubility and low bioavailability, structural modifications of its functional groups are made to generate novel lead(s) having better efficacy and less toxicity than the parent compound. BA analogue, 2c was found most potent inhibitor of colon cancer cell line, HT-29 cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 46 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…Autophagy is a dynamic process, and to estimate autophagic activity, it is essential to determine autophagic flux. Autophagy flux is defined as the whole process of cargo moving through the autophagy system, from phagophore formation to autophagosome formation, autophagosome‐lysosome fusion, and, eventually, cargo degradation and recycling . Under normal conditions, p62 binds to ubiquitinated substrates and to LC3 to be degraded along with its cargo.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a dynamic process, and to estimate autophagic activity, it is essential to determine autophagic flux. Autophagy flux is defined as the whole process of cargo moving through the autophagy system, from phagophore formation to autophagosome formation, autophagosome‐lysosome fusion, and, eventually, cargo degradation and recycling . Under normal conditions, p62 binds to ubiquitinated substrates and to LC3 to be degraded along with its cargo.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy flux is defined as the whole process of cargo moving through the autophagy system, from phagophore formation to autophagosome formation, autophagosome-lysosome fusion, and eventually cargo degradation plus recycling. Autophagy is a dynamic, not static process, and TEM is the gold standard method for assessing the presence of autophagic vesicles, like autophagosomes, lysosomes, autolysosomes (Dutta et al, 2016). Autophagosomes are confirmed by transmission electron microscopy (TEM) as double-membrane organelles with diameters of about 0.3–0.9 μm in yeast (Baba et al, 1997) and 0.5–1.5 μm in mammals (Mizushima et al, 2002).…”
Section: Autophagy and Autophagy Fluxmentioning
confidence: 99%
“…Furthermore, BA or BA analog could induce autophagy in HeLa, A549, MCF7, SW480 and HT29 cells, and autophagic salvage counterbalanced BA-induced cell death in HeLa cells. 10 , 37 Although studies observed that BA could induce autophagy, the role of autophagy as a cell death mechanism was not minutely addressed for BA-treated CRC cells.…”
mentioning
confidence: 99%